2008
DOI: 10.1111/j.1600-0609.2008.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis: new players, newer insights

Abstract: Iron is an essential element for virtually all-living organisms. It is required as a cofactor for a multitude of proteins of diverse biological function. Iron plays a central role in the formation of hemoglobin and myoglobin and in many vital biochemical pathways and enzyme systems including energy metabolism, neurotransmitter production, collagen formation and immune system function. As a transition metal, iron also has useful ligand-binding and redox properties. At the same time, iron poses enormous problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 136 publications
(133 reference statements)
2
35
0
4
Order By: Relevance
“…Some cells, such as reticuloendothelial macrophages and hepatocytes, are specialized in storing iron, and act to maintain a reserve that can be mobilized when needed [39]. Iron overload due to excessive absorption of dietary iron or as a result of frequent blood transfusions results in serious clinical manifestations including liver cirrhosis, tissue hemorrhage, atherosclerosis, cancer and diabetes [18,40,41]. In macrophages, iron excess inhibits expression of inducible NO synthase and impairs production of NO, an essential effector against infectious pathogens and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some cells, such as reticuloendothelial macrophages and hepatocytes, are specialized in storing iron, and act to maintain a reserve that can be mobilized when needed [39]. Iron overload due to excessive absorption of dietary iron or as a result of frequent blood transfusions results in serious clinical manifestations including liver cirrhosis, tissue hemorrhage, atherosclerosis, cancer and diabetes [18,40,41]. In macrophages, iron excess inhibits expression of inducible NO synthase and impairs production of NO, an essential effector against infectious pathogens and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it was shown that ID decreased expression of dopamin receptors, disrupted myelinization or disrupted the function of various enzymes involved in the nerve tissue (17)(18)(19). Again, another important yet controversial clinical effect of iron deficieny is its effects on the immune system (20)(21)(22). In addition, it was shown that IDA was strongly related with febril convulsions in some recent studies and in a meta-analysis performed in 2010 (23,24).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…It should be noted that the host is forced to maintain a certain level of bioavailable iron for cellular metabolic needs and thus employs intricate mechanisms to maintain iron balance. This is demonstrated by the observation that depriving cells of intracellular iron leads to rapid cell death (Edison et al, 2008 ). Conversely, if dietary or genetic factors shift the balance to a condition of iron overload, mammals are less able to resist infections (Bullen, 1981 ).…”
Section: Host -Iron Metabolismmentioning
confidence: 99%
“…Upon absorption, iron is bound by transferrin, which is secreted into the plasma and traffi cked to tissues so that iron can be delivered throughout the body. In a healthy individual, virtually all extracellular iron is bound by transferrin, accounting for about 0.1% of total iron within the organism (Edison et al, 2008 ). Due to the high affi nity of transferrin for iron and the fact that only about 30% of transferrin is iron saturated at any given time, the extracellular concentration of free iron within vertebrates is extremely low (Sarkar, 1970 ).…”
Section: Host -Iron Metabolismmentioning
confidence: 99%
See 1 more Smart Citation